Studying Some Chemical and Microbial properties of Mozzarella Cheese Produced (Damascus University Journal of agriculture sciences, 2021)
The research aimed to evaluate mozzarella cheese utilized in the manufacturing of locally pizza. Chemical and microbial analysis were conducted on 50 mozzarella cheese samples purchased from Damascus, Damascus Countryside, Darah, Al-Ghab and Aleppo Countryside through a year. The results revealed that the studied cheese samples exhibited lower fat and moisture contents comparing with the Syrian Standardization. Moreover, there were fluctuations in the salinity and acidity percentages among the samples.On the other hand, the microbial observations showed elevated levels of coliform and yeast and Staphylococcus aureus and hence indicated improper maturation, packaging and storage procedures, even though the product was cooked and kneaded at high temperature. Nevertheless, E. coli, Salmonella and Listeria were absent in the studied cheese samples, and consequently, consuming mozzarella cheese is considered safe, however, improvement in the whole processing conditions of mozzarella cheese are required.
Keywords: Pizza cheese; Mozzarella; chemical; microbial properties